Stratification of risks of tuberculosis relapses during the pandemic of the novel coronavirus infection - S. V. Smerdin; N. N. Sheshelyakina; A. I. Shevchenko; M. A. Plekhanova; R. I. Ludanny; T. I. Vorobieva (Туберкулез и болезни лёгких)
The objective: to assess risk factors for tuberculosis relapse during the COVID-19 pandemic.Results. During the retrospective study, medical documents of patients treated for tuberculosis in 2020-2022 were analyzed. 140 patients above 18 years old with confirmed tuberculosis were included: newly diagnosed tuberculosis – 50 patients, early relapses – 50 patients, and late relapses – 40 patients. At the first stage, significant factors for relapse development were identified (ANOVA): diabetes (F=19402,8; p=0,000000), substances abuse (F=547,6; p=0,000000), alcohol abuse (F=149,7; p=0,000000), MDR MTB (F=107,8; p=0,000000), HIV infection (F=72,4; p=0,000000), imprisonment (F=49,5; p=0,000000), chronic respiratory diseases (F=47,1; p=0,000000), smoking (F=29,0; p=0,000000), and social status (F=28,9; p= 0,000000). At the second stage (cluster analysis), factors implementing the risks of development of early or late relapses were identified.As well as before the COVID-19 pandemic, social, medical and biological risk factors play a significant role in the development of tuberculosis relapses; history of COVID-19 was not one of the risk factors; and stratification of the risk factors made it possible to identify factors that contribute to development of both early and late relapses and to determine preventive measures.